Continuous perioperative supraoccipital cisternal drainage - Palma, Eduardo; Rodríguez Martínez, Ricardo J; Pérez Lagrave, Alfredo; Palma, Liliana (Cirugía del Uruguay, 1976)
The technique of continuous supraoccipital cisternal peroperatory drainage in order to perform intra craneal decompression, through a. slow and progressive evacuation of spinal fluid from the ventricles and basilar cysterns is described. The procedure was used in 8 patients, without problems, obtaining good results and an important decompression. In 4 cases of intracraneal aneurysm, a clear endocraneal hypotension was obtained; in 4 cases of intracerebral tumors, it was obtained onJy reduction of intracraneal hypertension, and gene·ral antihypertensive treatment had to be associated. Supraoccipital cisterna! drainage will evacuate intracraneal fluid, but not th